Penguatan pendidikan karakter melalui pelatihan penggunaan aplikasi kindfull-digital character book - Azmi Fitriati; Subuh Anggoro; Sri Harmianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Kindfull-digital character book is a character monitoring application based-android and website. Its use is an alternative instrument for strengthening character education. This application made the character monitoring process easier, faster and more precise than the manual process. The purposes of this activity are to introduce, develop and provide skills in using the kindfull-digital character book application as an effective and efficient monitoring instrument for student character. The target users were teachers, parents and students. The method were used training, workshops and assistance in the use of information technology. This, results showed that are easy to learn and operate by users and are easily adapted to user needs. Monitoring this digital character through self-assessment, so it emphasizes the honesty of students, parents and teachers. Based on the results of the evaluation, users felt the usefulness and ease of using the application. Teachers and parents can work together in strengthening student character education. Economically, this application can be used repeatedly, by adding the desired character indicator. Teachers are no longer preoccupied with technical activities but can concentrate on strengthening student character.